Problems of the Language in Religion - Yuliani (International Journal of Science and Society, 2020)
The purpose of this paper is to describe the problems related to language that arise in religion. Religion in its teachings and dissemination cannot escape from the use of language, especially in every religious scripture that exists. The use and choice of language in religion is also often the cause of the complexity of realizing tolerance in religion. This research uses available literature studies related to language and religion. The author concludes that Language is a key player in a religion in terms of both teaching and teaching.